Optimizing Medication Outcomes in Neurocritical Care: Focus on Clinical Pharmacology - Rhoney, Denise H.; Morbitzer, Kathryn; Hatton-Kolpek, Jimmi (Seminars in Neurology, 2016)
Drug dosing in neurocritically ill patients presents enormous challenges for clinicians due to the complex pathophysiological alterations. These alterations are dynamic both between and within patients. Unpredictable exposure from standard dosing regimens, which were extrapolated to intensive care unit patients from healthy volunteer studies, may influence medication outcomes. Knowledge of potential alterations in pharmacokinetics/pharmacodynamics in these patients could be applied to maximize the clinical response and minimize adverse effects. Recognizing potential confounding clinical and treatment factors affecting drug response is an important step, but it is not enough. Overcoming absorption and distribution challenges by using specialized formulations and delivery systems is an area of active research. Improved methods for measuring drug concentrations in clinical settings across different matrices are also needed. Even with these advances, defining endogenous mediators signaling drug-target activation is necessary. Identifying biomarkers in disease and changes when a drug has reached its target will be pivotal. This information will improve our understanding of the pharmacogenomic and pharmacokinetic variables affecting pharmacodynamic endpoints across a spectrum of neurologic diseases.
Keywords: pharmacokinetics; critical care; neurocritical care